The characteristics and correlation of the microbial communities and flavors in traditionally pickled radishes. (January 2020) - Rao, Yu; Tao, Yufei; Chen, Xing; She, Xiao; Qian, Yang; Li, Yalin; Du, Yuwei; Xiang, Wenliang; Li, Hehe; Liu, Lei
Abstract: Pickled radish produced using the traditional fermentation method that radishes being fermented with the aged brine in the pottery altar is exceptionally popular and widely consumed around China. Although this traditional technique is usually associated with the production of high-quality fermented radish, the main features of radish prepared using this method remain unclear. This study revealed the characteristics of microbial diversity and flavors in radish fermented with aged brine in traditional pottery containers. At the phylum level, Firmicutes was the highest during the fermentation process. At the genus level, the abundance of Lactobacillus dominated. As for fungal composition, Pichia and Candida were the main genera, and the abundance of Pichia was significantly higher than Candida . This study also identified the volatile flavor compounds, some of them for the first time, and PCA revealed the separation between samples was dominated by dimethyl trisulfide and piperidine-2-thione. The correlation analysis suggested that Lactobacillus was negatively associated with 13 flavors, of which ten flavors were free amino acids (FAA). Enterobacteriaceae unclassified was correlated positively with 18 flavors, of which 14 were FAA. This study provided insight into the characteristics of fermented pickles produced using traditional fermentation techniques, and the relationship between microbiota and flavors. Highlights: Radishes were fermented with aged brine in traditional pottery containers. Lactobacillus and Pichia were the absolute dominant bacterium and fungi, respectively. Specific volatile flavor substances are identified by GC-MS. PCA revealed dimethyl trisulfide and piperidine-2-thione dominated the separation. The correlation between bacteria and flavors are visualized with bioinformatic tools.